State of Art of Pipeline Distribution of Oil Products in Kenya-Threats, Challenges and Prospects - Simbiri, Antony Fundia; Joel, Ogbonna F.; Okoro, Emmanuel E.; Oyoo, Daniel O. (European Journal of Applied Sciences, 2023)
Finally, in 2012, Kenya hit significant commercial oil deposits that could potentially, position it among prospective world oil exporters. Unparalleled expectations from this find is arousing long dead pipedreams of economic bonanza and overnight transformation among all stakeholders. However, to avail this resource to the markets, for the expected fiscal changes to occur, it has to be transported. This paper, therefore, seeks to microscopically review the current status of the pipeline transport of oil products in Kenya in the last decade. A summarized outlook of pipeline oil distribution globally is availed, especially in well-developed oil jurisdictions. This is sequenced with a comprehensive history of oil pipeline transport in the country. The flow mechanism of white and black oil products in pipelines is then briefly addressed in view of the waxy Turkana oil. A sneak preview of the legal landscape on oil pipeline transport in Kenya is likewise highlighted. The current content and context of pipelines, flow of white and black oil products in pipelines, and new pipeline infrastructure are then discussed with Kenya Pipeline Company Limited as the central denominator. Additionally, assertions on the upcoming new crude oil pipeline are evaluated. Finally, it exposes the prospects and challenges in the pipeline transport of oil products and sums up with vials of viable recommendations for its long term progress.